A metabolic syndrome in terrestrial ectotherms with different elevational and distribution patterns. Issue 10 (13th March 2018) - Žagar, Anamarija; Carretero, Miguel A.; Marguč, Diana; Simčič, Tatjana; Vrezec, Al
Abstract : The metabolic performance of ectotherms is expected to be driven by the environment in which they live. Ecologically similar species with contrasting elevation distributions occurring in sympatry at mid‐elevations, provide good models for studying how physiological responses to temperature vary as a function of adaptation to different elevations. Under sympatry, at middle elevations, where divergent species ranges overlap, sympatric populations are expected to have similar thermal responses, suggesting similar local acclimation or adaptation, while observed differences would suggest adaptation to each species' core range. We analysed the metabolic traits of sympatric species pairs from three ectotherm groups: reptiles (Reptilia: Lacertidae), amphibians (Amphibia: Salamandridae) and beetles (Coleoptera: Carabidae), living at different elevations, in order to test how adaptation to different elevations affects metabolic responses to temperature. We experimentally tested the thermal response of respiration rate (RR) and estimated potential metabolic activity (PMA) at three temperature regimes surrounding the groups' optimal activity body temperatures. RR was relatively similar among groups and showed a positive response to increasing temperature, which was more pronounced in the high‐elevation species of reptiles and beetles. Relative to RR, PMA displayed a stronger and more consistent positive response to increased temperature in all three groups. For all three groups, the average biochemical capacity for metabolism (PMA) was higher in the range‐restricted, high‐elevation species, and this difference increased at higher temperatures in a consistent manner. These results, indicating consistent pattern in three independently evolved animal groups, suggest a ubiquitous adaptive syndrome and represent a novel understanding of the mechanisms shaping spatial biodiversity patterns. Our results also highlight the importance of geographic patterns for the mechanistic understanding of adaptations in physiological traits, including species' potential to respond/adapt to global climate changes.